Reclassification of Paenibacillus riograndensis as a Genomovar of Paenibacillus sonchi: Genome-Based Metrics Improve Bacterial Taxonomic Classification - Sant’Anna, Fernando H.; Ambrosini, Adriana; de Souza, Rocheli; de Carvalho Fernandes, Gabriela; Bach, Evelise; Balsanelli, Eduardo; Baura, Valter; Brito, Luciana F.; Wendisch, Volker F.; de Oliveira Pedrosa, Fábio; de Souza, Emanuel M.; Passaglia, Luciane M. P. (Frontiers in Microbiology, 2017)
Species from the genus Paenibacillus are widely studied due to their biotechnological relevance. Dozens of novel species descriptions of this genus were published in the last couple of years, but few utilized genomic data as classification criteria. Here we demonstrate the importance of using genome-based metrics and phylogenetic analyses to identify and classify Paenibacillus strains. For this purpose, Paenibacillus riograndensis SBR5T, Paenibacillus sonchi X19-5T, and their close relatives were compared through phenotypic, genotypic and genomic approaches. With respect to P. sonchi X19-5T, P. riograndensis SBR5T, Paenibacillus sp. CAR114, and Paenibacillus sp. CAS34 presented ANI (average nucleotide identity) values ranging from 95.61% to 96.32%, gANI (whole-genome average nucleotide identity) values ranging from 96.78% to 97.31%, and dDDH (digital DNA-DNA hybridization) values ranging from 68.2% to 73.2%. Phylogenetic analyses of 16S rRNA, gyrB, recA, recN, and rpoB genes and concatenated proteins supported the monophyletic origin of these Paenibacillus strains. Therefore, we propose to assign Paenibacillus sp. CAR114 and Paenibacillus sp. CAS34 to P. sonchi species, and reclassify P. riograndensis SBR5T as a later heterotypic synonym of P. sonchi (type strain X19-5T), with the creation of three novel genomovars, Paenibacillus sonchi genomovar Sonchi (type strain X19-5T), Paenibacillus sonchi genomovar Riograndensis (type strain SBR5T), Paenibacillus sonchi genomovar Oryzarum (type strain CAS34T = DSM 102041T; = BR10511T).